Direct estimation of hydraulic parameters relating to steady state groundwater flow. (December 2016) - Sun, Kerang; Goltz, Mark N.
Abstract: Groundwater as an important, life-sustaining resource for humankind is being threatened by massive over-extraction and wide-spread contamination. Wise development and protection of this crucial resource requires a thorough understanding of groundwater flow in the subsurface. This paper presents a novel direct method to estimate important hydraulic parameters characterizing steady state groundwater flows for confined and unconfined isotropic aquifers. The method is appropriate for application in aquifers where horizontal flow dominates. The governing equations for the direct estimation method are superposed extensions of the well-known Thiem equation governing steady-state radial flow toward a pumping well under confined and unconfined conditions. This new approach has the following advantages over conventional methods: (1) simultaneously provides estimates of both hydraulic conductivity and hydraulic gradient, (2) can be applied using historical data without the need to conduct a pumping test, and (3) is a simple analytical method that can be applied easily. Verification of the direct estimation method is achieved by applying it to hypothetical homogeneous and heterogeneous aquifers simulated by three-dimensional finite element models. The usefulness of the method is also demonstrated with data from an actual field site. Highlights: Two dimensional steady state flow in confined and unconfined aquifers. Assessment of aquifer parameters using long term pumping and piezometric head data. Concurrent estimation of aquifer permeability and groundwater discharge rate.